2002
DOI: 10.1002/art.10335
|View full text |Cite
|
Sign up to set email alerts
|

A pulse‐chase study tracking the conversion of macrophage‐endocytosed serum amyloid A into extracellular amyloid

Abstract: Objective. To determine whether serum amyloid A (SAA) is internalized by and processed in macrophages en route to deposition as extracellular amyloid.Methods. SAA was tracked in cultures of peritoneal macrophages, using a pulse-chase protocol. Conclusion. The results of this study provide direct evidence that SAA internalized by and processed in macrophages forms extracellular amyloid. Based on the presence of 125 I-AA protein in macrophage lysates prior to the appearance of extracellular TxR-labeled amyloid, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
42
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 55 publications
(43 citation statements)
references
References 19 publications
1
42
0
Order By: Relevance
“…Mononuclear phagocytes are physiologically involved in SAA catabolism through endocytosis and trafficking to lysosomes, where the protein undergoes degradation. A role in initiating amyloid A fibril formation by mononuclear phagocytes was originally postulated on the basis of the presence of AA amyloid fibrils both in intracellular vesicles and close to the cell membrane in amyloid-laden tissues (4) and has been subsequently demonstrated in cell culture models (5). Studies in human monocyte cell lines have shown accumulation of newly formed AA amyloid fibrils in intracellular lysosomal compartments, indicating that aberrant processing of SAA is relevant in the pathogenesis of AA amyloidosis (6).…”
Section: General Mechanisms Of Aa Amyloidogenesismentioning
confidence: 99%
“…Mononuclear phagocytes are physiologically involved in SAA catabolism through endocytosis and trafficking to lysosomes, where the protein undergoes degradation. A role in initiating amyloid A fibril formation by mononuclear phagocytes was originally postulated on the basis of the presence of AA amyloid fibrils both in intracellular vesicles and close to the cell membrane in amyloid-laden tissues (4) and has been subsequently demonstrated in cell culture models (5). Studies in human monocyte cell lines have shown accumulation of newly formed AA amyloid fibrils in intracellular lysosomal compartments, indicating that aberrant processing of SAA is relevant in the pathogenesis of AA amyloidosis (6).…”
Section: General Mechanisms Of Aa Amyloidogenesismentioning
confidence: 99%
“…3 These data indicate that LC toxicity may contribute to cardiac dysfunction as well as play a role in amyloid fibril deposition. Furthermore, internalization of LCs (1,6, and 3 subtypes) by cardiac fibroblasts resulted in enhanced sulfation of secreted glycosaminoglycans (GAGs) with minimal heparan-sulfated proteoglycans localized within the cytoplasm. 4 These results supported earlier studies demonstrating an increase in GAGs with amyloid deposition.…”
mentioning
confidence: 99%
“…Models of AA and A␤ amyloid suggest that endocytosis and/or pinocytosis may be critical to amyloid protein internalization. 6,7 In addition, studies using mesangial cells demonstrate that internalization of LCs by cells utilizes a specific receptor complex pathway. 8,9 In neuronal cells, investigators showed that receptors of advanced glycation end products function as signal-transducing cell surface acceptors for A␤.…”
mentioning
confidence: 99%
“…Mixed cultures of SAA-producing hepatoma cells or hepatocytes and macrophages have been reported to produce AA fibrils in tissue culture. 25 A single published mixed culture experiment with human bone marrow cells and macrophages from an amyloid patient suggested a similar process. 91 More recent studies in which L-chains isolated from patients with AL and light chain deposition disease were incubated with cultured human mesangial cells seem to demonstrate cleavage of the amyloidogenic L-chains with subsequent fibril formation, a very interesting result awaiting confirmation in other laboratories.…”
Section: Interfaces Between the Amyloidoses And The Immune Systemmentioning
confidence: 99%
“…24,25 In this instance, there are few experimental data available regarding the details of these processes. In the case of the homotetrameric protein transthyretin (TTR), a shift in the equilibrium between tetramer and monomer leads to the enhanced population of a monomer pool predisposed to misfold.…”
Section: Mechanisms Of Amyloidogenesis In Humansmentioning
confidence: 99%